Seasonal and interannual variability of the Eastern Tropical Pacific Fresh Pool. Issue 3 (4th March 2017) - Guimbard, S.; Reul, N.; Chapron, B.; Umbert, M.; Maes, C.
Abstract: The Eastern Pacific Fresh Pool (EPFP) is a large region of low sea surface salinity (SSS) defined by values lower than 34 practical salinity scale within (5°S–30°N, 75°W–180°W). The fresh pool dynamically responds to strong regional and seasonally varying ocean‐atmosphere‐land interactions (including monsoon rain, trade and gap winds, and strong currents). Using more than 5 years of Soil Moisture and Ocean Salinity (SMOS) satellite sea surface salinity (SSS) and complementary satellite wind, rain, currents, and sea surface temperature data together with a historical ensemble of in situ products, the present study explores the seasonal and interannual dynamics of the fresh pool over the period 2004–2015. An important interannual variability of the maximal surface extension of the EPFP over the past decade is revealed with two extreme events (2012, 2015) occurring during the SMOS satellite period. These extremes are found to be related to the El Niño‐Southern Oscillation (ENSO) phases and associated anomalies of precipitation, surface currents, and trade wind in the central Pacific. In 2012 (La Niña), stronger trade winds coupled with a deficit of precipitation induced a minimum extension of the pool during the rainy season. Whereas, during the strong El Niño 2014–2015, the EPFP extension reached an unprecedented maximum value. A modification of the atmospheric freshwater fluxes and ocean surface currents during winter 2014 is found to have favored the onset of this abnormal fresh event. Key Points: Satellite SSS in synergy with complementary EO data allows studying the seasonal and interannual dynamics of the Eastern Pacific Fresh Pool Fresh pool zonal displacements and links between surface and subsurface processes respond to freshwater fluxes, wind stress, and currents Fresh pool interannual variability is related to ENSO phases, a maximal extension was reached in 2015 coinciding with a strong El Nino event